Efficient Timing Offset Estimation Method Tailored for ACO-OFDM VLC Systems - Wang, Kaiyao; Liu, Yongjun; Hong, Zhiyong; Zeng, Zhiqiang (Journal of lightwave technology, 2022)
The asymmetrically clipped optical orthogonal frequency division multiplexing (ACO-OFDM)-based visible light communication (VLC) system has received widespread attention due to its capability to support high spectrum efficiency as well as high power efficiency. The accuracy of symbol timing offset estimation is a critical factor limiting the performance of ACO-OFDM. In order to cope with this challenge, a training symbol-aided symbol timing synchronization method tailored for ACO-OFDM is put forward. The influence of the design of training symbol structure and timing metric on the synchronization accuracy is investigated, and three timing metrics are presented to supply simple and efficient timing offset estimation by utilizing the structure of odd-even mirror-symmetric and complementary symmetric of the newly designed training symbol. In addition, the system bit error rate (BER) penalty induced by timing synchronization error is analyzed, and the approximate relationship between BER performance loss and timing estimation error probability and ideal BER performance is presented. Simulation is used to assess the performance of the three proposed timing metric methods in different channel environments, and they are compared with the two existing timing synchronization algorithms in ACO-OFDM, namely the modified Park method and the Tian method. The results show that the new synchronization method is superior to the comparison methods concerning achievable synchronization accuracy and system BER penalty.